Forest Carbon Supply in Nepal : Evidence from a Choice Experiment - Dissanayake, Sahan; Bluffstone, Randall A.; Somanathan, E.; Luintel, Harisharan; Paudel, N. S.; Toman, Michael A. (World Bank, Washington, DC, 2018)
This paper uses a choice experiment conducted in Nepal during 2013 to estimate household-level willingness to participate in a village-level program under the Reduced Emissions from Deforestation and Forest Degradation initiative requiring reductions in fuelwood collection, as a function of the price paid per unit of avoided carbon dioxide emissions. The analysis examines incentives to participate both in villages having formal community forest management, the core institution for implementing Reduced Emissions from Deforestation and Forest Degradation, and villages having only informal forest user groups. Contrary to previous findings in the literature about participation incentives, but in keeping with other recent studies of Reduced Emissions from Deforestation and Forest Degradation pilots in Nepal, this study finds that relatively little emission reduction would take place at prices of $1.00 to $5.00 per ton of avoided carbon emissions. Formal community forests will almost certainly be the core institution within which Reduced Emissions from Deforestation and Forest Degradation is implemented in Nepal and likely other countries. The study finds that average and median values of payment required for agreement to reduce fuelwood collection are substantially larger for formal forest user groups than in informal communities. This reflects that formal groups likely already have fuelwood collection restrictions in place, whereas informal groups may de facto permit open access extraction. The analysis also suggests that households that are part of informal groups react to Reduced Emissions from Deforestation and Forest Degradation very differently than households that are formal group members. Broadly speaking, "underprivileged" formal group member households, such as those who are landless, female-headed, and poor, appear to be warier of fuelwood collection restrictions and thus require higher payments than average respondents. This difference does not appear to carry over to informal group members.